Assisted Reproduction in Congenital Adrenal Hyperplasia - Chatziaggelou, Anastasios; Sakkas, Evangelos G.; Votino, Raffaella; Papagianni, Maria; Mastorakos, George (Frontiers in Endocrinology, 2019)
Congenital Adrenal Hyperplasia (CAH) is a group of autosomal recessive disorders characterized by defects of adrenal steroidogenesis due to mutations in one of the following enzymes: 21-hydroxylase (21OH), 11β-hydroxylase (11βOH), 17α-hydroxylase (17OH; also known as 17, 20-lyase), 3β hydroxysteroid dehydrogenase type 2 (3βHSD2), steroidogenic acute regulatory protein (StAR), P450 cholesterol side-chain cleavage (P450scc), and P450 oxidoreductase (POR). More than 95% of congenital adrenal hyperplasia cases are due to mutations in CYP21A2, the gene encoding the adrenal steroid 21-hydroxylase enzyme (P450c21). This work focuses on this type of CAH given that it is the most frequent one. This disease is characterized by impaired cortisol and aldosterone production as well as androgen excess. A variant of the CAH is the non-classic type of CAH (NCCAH), usually asymptomatic before the 5th year of age, diagnosed during puberty especially in patients visiting a fertility clinic. NCCAH is characterized mainly by anovulatory cycles and/or high androgen concentrations. Both types of CAH are associated with infertility. Given that the incidence of NCCAH is greater than that of CAH, patients suffering from NCCAH are more often diagnosed for the first time in a fertility clinic. Thus, screening for NCCAH should always be considered. The causes of infertility in CAH patients are multi-factorial including virilization of external genitalia, altered psychosocial development and hormonal disorders. The main challenges encountered in assisted reproduction are the androgen excess-associated anovulatory cycles as well as the increased circulating progesterone concentrations during the follicular phase which impact endometrial receptivity, tubal motility and cervical thickness. Administration of sufficient substitution dose of glucocorticoids usually resolves these problems and leads not only to successful assisted reproduction treatment but also to spontaneous pregnancy. Patients with CAH should be followed by a multidisciplinary team including gynecologist, endocrinologist and pediatrician.